Mental Health Outcomes Among Civil Servants Aiding in Coronavirus Disease 2019 Control - Hu, Qingqing; Hu, Xiaochu; Zheng, Beibei; Li, Lanjuan (Frontiers in Public Health, 2021)
Objective: To assess the psychiatric status of Chinese civil servants aiding in coronavirus disease 2019 (COVID-19) control. Background: During the COVID-19 pandemic, Chinese civil servants have faced high workloads that may contribute to mental disorders. We assessed the prevalence of both depression and anxiety symptoms among civil servants in Jiangsu and surrounding provinces using the Chinese versions of the 9-item Patient Health Questionnaire (PHQ-9) and the 7-item Generalized Anxiety Disorder (GAD-7) scale. Methods: The PHQ-9 and GAD-7 were used to assess the severity of symptoms of depression and anxiety, respectively. Multivariable logistic regression analysis was performed to identify factors associated with mental health outcomes. Results: In total, 867 Chinese civil servants aiding in COVID-19 control were included in our study. Overall, 37.25% and 38.06% of all respondents reported having symptoms of depression and anxiety, respectively. Respondents who were younger and more educated and those who had fewer years of work experience had higher scores for both depression and anxiety. Multivariable logistic regression analysis showed that being a woman, being younger, having more education and having fewer years of work experience were associated with a higher risk of symptoms of depression and anxiety. However, whether they had experience combating infectious diseases or worked in frontline, there was no significant difference between respondents with and without experience, as well as between frontline and nonfrontline workers, in both symptoms of depression and anxiety. Conclusions: The civil servants aiding in COVID-19 control reported suffering from varying degrees of mental disorders. Therefore, more attention should be devoted to the psychological distress of these civil servants.